Efektivitas Penerapan Ice Breaking terhadap Motivasi Belajar Siswa Kelas VI MIN 9 Langkat - Diah Hofizhatul Husnah; Dian Anggeraini (BADAN PENERBIT STIEPARI PRESS, 2024)
The research background is based on the importance of creating an interesting and enjoyable learning environment to increase student involvement in the learning process. The aim of the research is to systematically investigate the effectiveness of the ice breaking technique in increasing Madrasah Ibtidaiyah students' learning motivation towards learning. The method used in this research is literature study, which involves the steps of identification, evaluation and synthesis of findings from various related studies. The research results show that the application of ice breaking consistently contributes positively to student learning motivation. Findings from various literature sources show that ice breaking can create a relaxed, interactive and fun learning atmosphere, which in turn increases students' interest in learning Indonesian. Apart from that, ice breaking also helps strengthen the relationship between students and lesson material, as well as increasing participation and student involvement in the learning process. The implication of these findings is the importance of considering the use of ice breaking techniques in designing and implementing learning. Teachers and educational policy makers can use the results of this research as a basis for developing more innovative and effective learning strategies in increasing student learning motivation and strengthening the quality of education at the Madrasah Ibtidaiyah level.